Estudio de impacto ambiental expost del área minera chacra 1 (código 500567), parroquia Guaysimi, cantón Nangaritza, provincia de Zamora Chinchipe - Apolo Mori, Jorge Nicolay (2013)
The present search work was executed in the Guayzimi city of the canton Nangaritza jurisdiction of the Zamora Chinchipe province, which was realized the Environmental Impact Study Ex – Post, Chacra 1 mining area (Code 500567), to determine the environmental characteristics which has the area of intervention of the mining project and the issues that have the various actions involved in alluvial placer mining on it, in order to outline various measures that involve the protection and remediation of the area of influence both environmental and social. The methodology used to develop the study was conducted in three phases: the first phase consisted in the collection of bibliography information for the study area. The second phase was based on the performance of field work to obtain information: physical, biological and socioeconomic area, each of them through the use of tools and techniques specific, and the third phase was based on the interpretation of the information obtained (bibliographic and field), which defined the current situation locally, as well as actions leading to sustainable management. The work began with the implementation of environmental and socioeconomic diagnosis, to know the reality of the project area. Similarly, established mining processes developed in the mining area "Chacra 1", and through the cause and effect matrix, identified environmental factors that are altered by the activities taking place, as well as, the potentialities that are generated mainly socioeconomic derived of the present mining in the sector. Subsequently, I analyzed the results of the environmental assessment and based on them, were established strategic intervention lines that make up the management plan of the mining area, which are aimed at minimize the impacts to the natural environment by optimizing processes in operating activities and processing of minerals; provide security for workers at the concession area among others. The Management Plan of the study contemplates the following programs:  Impacts Mitigation and Prevention Program  Rehabilitation mined site Program  Health and Safety Program, Provision of personal protective equipment  Signage Program (Safety)  Training Program  Contingency Program  Monitoring and Control Program  Countervailing Measures Program  Closure Plan The estimated budget for the development of the various activities set out in the Environmental Management Plan proposed is 28120 USD. As a result of this study, I found that interacting environmental factors and mining area, is have measures that can help manage an adequate, effective and efficient this branch of production, controlling thereby the environmental and social effects.